Developing and Integrating Regular Training in Serious Incident Investigations and Coroner’s Inquests Into the Higher Trainees Teaching at Kent and Medway NHS and Social Care Partnership Trust (KMPT) - Maria Moisan; Chiara Rubino; Rachel Daly (BJPsych Open, 2025)
Aims: This project aims to develop and integrate regular training on Serious Incident (SI) Investigations and Coroner’s Inquests into the Higher Trainees Teaching at Kent and Medway NHS and Social Care Partnership Trust (KMPT). The goal is to enhance trainees’ understanding and confidence in these critical areas, ultimately improving patient safety and supporting psychiatric trainees in their professional development.